2005
DOI: 10.1590/s0001-37652005000300013
|View full text |Cite
|
Sign up to set email alerts
|

Modern sedimentation in the Cabo Frio upwelling system, Southeastern Brazilian shelf

Abstract: The analyses of U k 37 paleotemperatures and sedimentological parameters in box cores from the Cabo Frio upwelling zone, southeastern Brazil, were used to understand the modern sedimentation as well as to evaluate the role played by the upwelling process in the sedimentary patterns.Three box-cores located closer to the upwelling area show a general trend of cooling waters taking place in the last 700 years. Since the present upwelling is dependent on local and remote wind regime, a phase of dominating NE winds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
26

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 22 publications
(17 reference statements)
1
32
0
26
Order By: Relevance
“…The upwelling itself occurs when a prevailing northeasterly trade wind dominates in the region (Calado et al, 2008) as a result of a north-south to east-west change in the orientation of the South American shoreline. The intense and constant flow of the BC and NBC waters, accompanied by a relatively low volume of regional fluvial terrigenous sediment delivery, makes the Southwestern Atlantic coast a region of low sedimentation rates (Mahiques et al, 2005). Along the Southwestern Brazilian coast the BC occupies the top 200 m of the water column.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The upwelling itself occurs when a prevailing northeasterly trade wind dominates in the region (Calado et al, 2008) as a result of a north-south to east-west change in the orientation of the South American shoreline. The intense and constant flow of the BC and NBC waters, accompanied by a relatively low volume of regional fluvial terrigenous sediment delivery, makes the Southwestern Atlantic coast a region of low sedimentation rates (Mahiques et al, 2005). Along the Southwestern Brazilian coast the BC occupies the top 200 m of the water column.…”
Section: Site Descriptionmentioning
confidence: 99%
“…In the Cabo Frio system, Laslandes et al (2006) suggested that the influence of "El Niño" events has been increasing over the last four thousand years and upwelling processes must have been associated with the predominance of northeasterly winds for about the last 2,400 years. Moreover, climatic changes in the last 1,000 to 3,000 years could have intensified upwelling events during the last seven hundred years (MAHIQUES et al, 2005). It has been suggested that the upwelling events in the Benguela system started ten million years ago (SIESSER, 1980).…”
Section: Global Changes and Local Impactsmentioning
confidence: 99%
“…An increase in upwelling intensity has been suggested for the Canary (MCGREGOR et al, 2007) and Benguela systems and may be a function of the superficial Atlantic circulation (MARLOW et al, 2000). However, a rise in temperature and water level has been reported on the southwestern coast of the USA (ROEMMICH, 1992).…”
Section: Global Changes and Local Impactsmentioning
confidence: 99%
“…Discrete upwelling events may occur throughout the entire year but are more intense and frequent during the spring and summer months when a marked thermal dome forms just below the surface (reviewed by GUIMARAENS et al, 2005). Sedimentation rates in the upwelling zone of Cabo Frio range from 0.26 to 0.66 mm.year-1 (MAHIQUES et al, 2005). The non-upwelling period in Cabo Frio is characterized by warm waters that occur during fall and winter and have temperatures generally above 21 ºC and nutrient concentrations of nitrate and phosphate are below 1 and 0.4 μg-at.-, respectively.…”
Section: Methodsmentioning
confidence: 99%